Cold dust and young starbursts: spectral energy distributions of Herschel SPIRE sources from the HerMES survey - Rowan-Robinson, M; Roseboom, I; Vaccari, M; Amblard, A; Arumugam, V; Auld, R; Aussel, H; Babbedge, T; Blain, A; Bock, J; Boselli, A; Brisbin, D; et al. (2010)
We present spectral energy distributions (SEDs) for 68 Herschel sources detected at 5σ at 250, 350 and 500 μm in the HerMES SWIRE-Lockman field. We explore whether existing models for starbursts, quiescent star-forming galaxies and active galactic nucleus dust tori are able to model the full range of SEDs measured with Herschel. We find that while many galaxies ( 56 per cent) are well fitted with the templates used to fit IRAS, Infrared Space Observatory (ISO) and Spitzer sources, for about half the galaxies two new templates are required: quiescent ('cirrus') models with colder (10-20 K) dust and a young starburst model with higher optical depth than Arp 220. Predictions of submillimetre fluxes based on model fits to 4.5-24 μm data agree rather poorly with the observed fluxes, but the agreement is better for fits to 4.5-70 μm data. Herschel galaxies detected at 500 μm tend to be those with the highest dust masses. © 2010 The Authors. Journal compilation © 2010 RAS.